2013
DOI: 10.1371/journal.pone.0057485
|View full text |Cite
|
Sign up to set email alerts
|

High Humidity Leads to Loss of Infectious Influenza Virus from Simulated Coughs

Abstract: BackgroundThe role of relative humidity in the aerosol transmission of influenza was examined in a simulated examination room containing coughing and breathing manikins.MethodsNebulized influenza was coughed into the examination room and Bioaerosol samplers collected size-fractionated aerosols (<1 µM, 1–4 µM, and >4 µM aerodynamic diameters) adjacent to the breathing manikin’s mouth and also at other locations within the room. At constant temperature, the RH was varied from 7–73% and infectivity was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
168
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(186 citation statements)
references
References 31 publications
(53 reference statements)
7
168
0
2
Order By: Relevance
“…Influenza virus survival exhibited a canonical dip between 40% and 80% RH in many studies (Harper, 1961;Hemmes et al, 1962;Lowen et al, 2007;Noti et al, 2013). For nearly all cases, virus survival declined relative to increased length of exposure.…”
Section: Knowledge Gapsmentioning
confidence: 99%
See 4 more Smart Citations
“…Influenza virus survival exhibited a canonical dip between 40% and 80% RH in many studies (Harper, 1961;Hemmes et al, 1962;Lowen et al, 2007;Noti et al, 2013). For nearly all cases, virus survival declined relative to increased length of exposure.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…The virus literature featured a combination of laboratory testing (Akers et al, 1966;Lowen et al, 2007;McDevitt et al, 2010;Noti et al, 2013;de la Noue et al, 2014), epidemiology (Shaman and Kohn, 2009;Shaman et al, 2010;Barreca and Shimshack, 2012;van Noort et al, 2012;Jaakkola et al, 2014), modeling (Shaman and Kohn, 2009;Yang and Marr, 2011), and review papers (Morawska, 2006;Brankston et al, 2007;Weber and Stilianakis, 2008;Tang, 2009;Memarzadeh, 2012;; test conditions are shown in Figure 4. The review paper by Weber and Stilianakis (2008) identified three methods of transmission: droplet (sneezing or coughing), airborne, and contact; the review paper by Brankston et al (2007) also discussed influenza survival and transmission.…”
Section: Virusesmentioning
confidence: 99%
See 3 more Smart Citations